To be a scout. Mission: to change the world. (Journal of Parents and Teachers, 2017)
The dictionary defines scouting as: "Movement of youth that seeks the integral education of the individual through self-training and contact with nature."Scouting is the world's largest youth volunteer organization, with 40 million people in 162 countries, from different cultures, languages and religions working to build a better world.
Keywords: Informal education; social commitment; environment; plurality; leadership; scouting; scout; Integral education